The Undoing of the Subject: Levinas’ Thought on Ipseity - Ferro, Floriana (Scenari, 2021)
This paper focuses on Levinas’ concept of ipseity and on its change between the 1960’s and the 1970’s, arguing that this change implies the undoing of the subject. In Totality and Infinity (1961), ipseity is considered as the deep core of the I, whereas, in Otherwise Than Being (1974), it is the other person inside the self. Levinas also theorizes another kind of other-in-the-same, which is illeity, the trace of God inside the human soul. It is shown that illeity is not problematic for the subject, since it does not cause its undoing. Furthermore, it is argued that ipseity, in Otherwise Than Being, is not a mere opening to alterity, but a source of alienation. Finally, it is shown that Levinas starts to change his mind on ipseity in 1968 (“Substitution”), however this modification becomes clear only in 1970 (“No Identity”).